Evaluation of Seismic Demand on Nonstructural Elements Based on Shake-Table Testing of Full-Scale 2-Story Steel Moment Frame - Jun, Su Chan; Lee, Cheol Ho; Bae, Chang Jun; Cho, Bong Ho (Journal of Earthquake Engineering, 2024)
A shake table test using a full-scale 2-story steel moment frame was conducted to investigate the peak floor acceleration (PFA) and the peak component acceleration (PCA), which directly affect the seismic demand on nonstructural elements. The main focus of this study was to evaluate the effects of structural and component nonlinearity on the nonstructural seismic demand. The PFA reduction suggested by ASCE 7-22 to account for structural nonlinearity was shown to be larger than the experimental results for low-to-moderate ductility levels. The analysis on the resonant PCA showed the importance of structural nonlinearity on the elastic CAR (=PCA/PFA). The high resonant PCA around the fundamental period of the elastic test frame (7 times PFA) was effectively decreased as the test frame experienced a moderate level of ductility; PCA was lowered by 36% and 25% on the 2nd and roof floors, respectively. The effect of component yielding on the PCA was evaluated based on the test results of steel racks mounted on flexible and rigid access floors. The PCA reduction depending on the component ductility level was less than the relevant provisions of ASCE 7-22, and the reason was discussed from the perspective of the pinched hysteretic behavior of the tested specimens.
Keywords: % reductions; Access floor; Floor accelerations; Non-structural elements; Nonlinear behaviours; Peak floor; Seismic demands; Shake-table tests; Steel moment frames; Structural nonlinearities; access floor; nonlinear behavior; Nonstructural elements; seismic demand; shake table test